Microwave-Assisted Green Synthesis of Silver Nanoparticles Using Juglans regia Leaf Extract and Evaluation of Their Physico-Chemical and Antibacterial Properties - Mahsa Eshghi; Hamideh Vaghari; Yahya Najian; Mohammad Javad Najian; Hoda Jafarizadeh-Malmiri; Aydin Berenjian (MDPI AG, 2018)
Silver nanoparticles (Ag NPs) were synthesized using Juglans regia (J. regia) leaf extract, as both reducing and stabilizing agents through microwave irradiation method. The effects of a 1% (w/v) amount of leaf extract (0.1–0.9 mL) and an amount of 1 mM AgNO3 solution (15–25 mL) on the broad emission peak (λmax) and concentration of the synthesized Ag NPs solution were investigated using response surface methodology (RSM). Fourier transform infrared analysis indicated the main functional groups existing in the J. regia leaf extract. Dynamic light scattering, UV-Vis spectroscopy and transmission electron microscopy were used to characterize the synthesized Ag NPs. Fabricated Ag NPs with the mean particle size and polydispersity index and maximum concentration and zeta potential of 168 nm, 0.419, 135.16 ppm and −15.6 mV, respectively, were obtained using 0.1 mL of J. regia leaf extract and 15 mL of AgNO3. The antibacterial activity of the fabricated Ag NPs was assessed against both Gram negative (Escherichia coli) and positive (Staphylococcus aureus) bacteria and was found to possess high bactericidal effects.